DISCLOSURE OF SUSTAINABILITY REPORTS: (Survey of BUMN & BUMD Banks Listed on the Indonesian Stock Exchange) - Ikram, Syafrizal; Fadjar, Achmad; Rachman, Andry (Faculty of Economic and Business, University of Pasundan, 2024)
The bank does not focus on profits but pays attention to the environment and social issues that lead to sustainable development. The Financial Services Authority (OJK) issued regulations regarding Technical Guidelines for Preparing Sustainability Reports. This research aims to determine the level of disclosure of sustainability reports in 2022 at state-owned banks and state-owned companies on the Indonesian Stock Exchange. The research method uses descriptive analysis, which describes the research object based on facts and then analyzes and interprets it. The research results on the level of disclosure of sustainability reports are very good, and show management's commitment to fulfilling disclosure obligations regarding environmental sustainability in economic, environmental, and social aspects. Companies need to improve and optimize programs such as environmentally friendly products, involvement of local parties with sustainable financial business processes, conservation, and biodiversity conversion efforts.